Crowdsourcing: A contemporary form of project management with linkages to open innovation and novel operations. Issue 6 (21st March 2018) - Wilson, Kathleen Bridget; Bhakoo, Vikram; Samson, Danny
Abstract : Purpose: The purpose of this paper is to link crowdsourcing, operations management (OM) and project management (PM). The study demonstrates how crowdsourcing as an open innovation mechanism is operationalised within a complex PM context. Specifically, the study seeks to understand how crowdsourcing as a novel form of OM improves key outcomes. Design/methodology/approach: The authors conducted exploratory research involving five pure-play crowdsourcing firms based in the USA and Australia. Findings: The findings indicate that the firms practise a form of crowdsourcing that allows flexible, efficient and low risk operations and links to contemporary notions of PM such as projectification and project society. The crowd can be used in a new manner to boost success factors tied to PM through open innovation and operational novelty. In terms of OM, crowdsourcing offers flexibility, speed, dynamism and scalability to project processes. Research limitations/implications: This research is based on five case studies. Further fine-grained, longitudinal research is required to fully understand this phenomenon in a wider range of contexts. Practical implications: The paper contributes to practices tied to open innovation and provides guidance on how organisations might use large crowds to enhance PM success. Originality/value: The study represents early scholarship on crowdsourcing and project operations. It makes three contributions. First, the authors introduce a new theoretical framework linking PM and novel aspects of crowdsourcing to extend understandings of projectification, as well as open innovation frameworks. Second, the authors showcase the flexibility and fluidity of the crowdsourcing project process. Third, the authors examine crowdsourcing operations in terms of size, efficiency and scalability which results in timely and efficient output due to innovative technology, along with the element of trust among stakeholders.